Valencia Agudelo, Germán Darío. (2019). Organizarse para negociar la paz: Gobernanza de la paz negociada en Colombia, 1981-2016. Medellín: Universidad de Antioquia. - Chaverra Colorado, Fredy Alexander (Estudios Políticos, 2020)
.